2022
DOI: 10.34306/att.v4i2.180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Artificial Intelligence in Smart City Air Purifier Systems

Abstract: Dirty air or air pollution is one of the many natural problems that we face, the problem of harmful air pollution is very representative of a colony. If the air conditioner is not healthy so that it disturbs human health. Referring to the World Most Most Polluted Country Index, Indonesia is one of 10 countries where the air is unhealthy or polluted, requiring solutions to these natural problems. This paper aims to find solutions and minimize the impact of wider air pollution through air purification by utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The adverse effects of poor air quality are well-documented and include respiratory and cardiovascular diseases, adverse impacts on ecosystems, and climate change [37]. Particulate matter, for instance, can penetrate deep into the lungs, leading to respiratory problems, while ground-level ozone is known to cause respiratory issues and other health problems [38].…”
Section: Related Work 21 Air Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of poor air quality are well-documented and include respiratory and cardiovascular diseases, adverse impacts on ecosystems, and climate change [37]. Particulate matter, for instance, can penetrate deep into the lungs, leading to respiratory problems, while ground-level ozone is known to cause respiratory issues and other health problems [38].…”
Section: Related Work 21 Air Qualitymentioning
confidence: 99%
“…One area that is attracting attention is the use of artificial intelligence (AI)-based air quality systems in educational settings [16]. The use of AI technology in air quality systems promises to make a positive contribution to the health and productivity of students and teaching staff [17], [18]. However, maintaining the long-term use of this system still faces challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This is vital for the integrity of the study, as it helps in avoiding overlap between constructs, ensuring that each contributes independently to our understanding of the purchasing decision process [33]. For instance, when assessing the distinct influence of product quality and influencers on purchasing decisions, discriminant validity ensures that the perceived value added by influencers is not merely a reflection of product quality perceptions or vice versa [34]. Establishing discriminant validity involves statistical tests, such as analyzing the APTISI Transactions on Technopreneurship (ATT) ❒ 15 crossloadings of items and comparing the square root of the average variance extracted (AVE) for each construct with the correlation between constructs] [35].…”
Section: Literature Review 211 Discriminant Validitymentioning
confidence: 99%
“…An M4A file features a hierarchical structure with various nested segments known as atoms or boxes [18] [64]. Existing research has demonstrated that re-encoding an M4A file leads to structural changes that differ from the original file [65].…”
Section: Changes In Audio File Structurementioning
confidence: 99%